2009
DOI: 10.1182/blood-2008-12-193458
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cytogenetics in patients with relapsed or refractory multiple myeloma treated with lenalidomide plus dexamethasone: adverse effect of deletion 17p13

Abstract: Although the combination of lenalidomide and dexamethasone is effective therapy for patients with relapsed/refractory multiple myeloma, the influence of high-risk cytogenetic abnormalities on outcomes is unknown. This subanalysis of a large, open-label study investigated the effects of the most common unfavorable cytogenetic abnormalities detected by fluorescence in situ hybridization, del(13q), t(4;14), and del(17p13), in 130 evaluable patients treated with this regimen. Whereas patients with either del(13q) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
108
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(114 citation statements)
references
References 24 publications
3
108
1
2
Order By: Relevance
“…3,4 Patients with del(13) and t(4;14) chromosomal abnormalities had lower ORRs and shorter median PFS and OS compared with those who did not have these abnormalities. These results partly contrast the MM-016 study by Reece et al, 10 which reported that relapsed and refractory MM patients treated with lenalidomide plus dexamethasone overcame poor prognosis conferred by the chromosomal abnormalities of del(13), t(4;14), but not del(17p), as evidenced by the findings that the advantage in TTP and OS conferred by the addition of lenalidomide to dexamethasone were independent of del(13) or t(4;14) abnormalities. However, the study also reported that both del(13q) and t(4;14) were associated with shorter TTP in univariate analyses, and that the ORRs in patients with del(13q), t(4;14), and del(17p13) (76.4, 78.6 and 58.3%, respectively) were lower than reported for the overall study population (83.1%).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…3,4 Patients with del(13) and t(4;14) chromosomal abnormalities had lower ORRs and shorter median PFS and OS compared with those who did not have these abnormalities. These results partly contrast the MM-016 study by Reece et al, 10 which reported that relapsed and refractory MM patients treated with lenalidomide plus dexamethasone overcame poor prognosis conferred by the chromosomal abnormalities of del(13), t(4;14), but not del(17p), as evidenced by the findings that the advantage in TTP and OS conferred by the addition of lenalidomide to dexamethasone were independent of del(13) or t(4;14) abnormalities. However, the study also reported that both del(13q) and t(4;14) were associated with shorter TTP in univariate analyses, and that the ORRs in patients with del(13q), t(4;14), and del(17p13) (76.4, 78.6 and 58.3%, respectively) were lower than reported for the overall study population (83.1%).…”
Section: Discussioncontrasting
confidence: 56%
“…9 Preliminary results from a study in patients with relapsed and refractory MM treated with lenalidomide plus dexamethasone showed that this combination can overcome the poor prognosis conferred by the chromosomal abnormalities of del (13) and t(4;14), but not del(17p). 10 In contrast, a recent analysis of 100 patients treated with lenalidomide plus dexamethasone at diagnosis revealed that this combination was not able to overcome the poor prognosis of chromosomal abnormalities and high labeling index. 11 The prognostic value of these cytogenetic abnormalities and the impact of prior therapy in the relapsed and refractory setting remain to be fully defined.…”
Section: Introductionmentioning
confidence: 98%
“…This detrimental effect of del17p has also been shown in previously treated patients who were treated with RD, 18 RD plus doxorubicin, 19 or in newly diagnosed patients treated with RD 20 or with bortezomib plus dexamethasone. 21 However, it is disappointing the fact that even combinations of the most active novel agents cannot overcome this effect, which is present in about 10% of patients, suggesting that new treatments and innovative approaches are urgently needed.…”
Section: Discussionmentioning
confidence: 83%
“…21 Two recent reports suggested that t(4;14) may not be as important in patients with relapsed or refractory MM treated with RD. However, these reports had quite different conclusions about the importance of del13q: Reece et al 18 suggested that RD overcomes the effect of del13q, whereas in the report of Avet-Loiseau et al del13q (by FISH) was an independent poor prognostic factor. The differences between these studies and our data can be explained by several factors: (a) differences in the characteristics of the patients that were included, (b) the inclusion of additional CAs (amp1q, del17p) in our multivariate models, (c) the relatively low numbers of patients with t(4;14) or del17p in our analysis; (d) a trend to imbalance in the number of patients with del13q detected by karyotype between RD and VRD (1 vs 6 patients, respectively); (e) the different dosage of dexamethasone used in our VRD regimen compared with the original RVD 8 and (f) the major prognostic impact of resistance to previous therapy, high LDH and extramedullary disease, which may mitigate the impact of CAs in the analysis.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, relapsed or refractory MM patients treated with lenalidomide plus dexamethasone exhibited comparable time to progression (TTP) and OS regardless of del13q or t(4;14) status, whereas patients with del17p13 experienced worse time-to-event outcomes. Similarly, the presence of a non-hyperdiploid karyotype, other poor-risk cytogenetic abnormalities [i.e., presence of del13q, del17p, add1q21, t(4;14), or t(14;16)], and thalidomide-refractory disease were associated with reduced responses (less than a PR) to treatment with lenalidomide and dexamethasone alone or in combination with bortezomib [11]. These findings suggest that the presence of high-risk karyotypic abnormalities which included chromosome 13, hypodiploidy, t(4;14), t(14:16) or 17p-may define subsets of patients more likely to benefit from targeted therapies [12].…”
Section: Discussionmentioning
confidence: 99%